Reproductive System Symbiotic Bacteria Are Conserved between Two Distinct Populations of Euprymna scolopes from Oahu, Hawaii - Kerwin, Allison H. (mSphere, 2018)
Female Hawaiian bobtail squid, Euprymna scolopes, harbor a symbiotic bacterial community in a reproductive organ, the accessory nidamental gland (ANG). This community is known to be stable over several generations of wild-caught bobtail squid but has, to date, been examined for only one population in Maunalua Bay, Oahu, HI. This study assessed the ANG and corresponding egg jelly coat (JC) bacterial communities for another genetically isolated host population from Kaneohe Bay, Oahu, HI, using 16S amplicon sequencing. The bacterial communities from the ANGs and JCs of the two populations were found to be similar in richness, evenness, phylogenetic diversity, and overall community composition. However, the Kaneohe Bay samples formed their own subset within the Maunalua Bay ANG/JC community. An Alteromonadaceae genus, BD2-13, was significantly higher in relative abundance in the Kaneohe Bay population, and several Alphaproteobacteria taxa also shifted in relative abundance between the two groups. This variation could be due to local adaptation to differing environmental challenges, to localized variability, or to functional redundancy among the ANG taxa. The overall stability of the community between the populations further supports a crucial functional role that has been hypothesized for this symbiosis. IMPORTANCE In this study, we examined the reproductive ANG symbiosis found in two genetically isolated populations of the Hawaiian bobtail squid, Euprymna scolopes. The stability of the community reported here provides support for the hypothesis that this symbiosis is under strong selective pressure, while the observed differences suggest that some level of local adaptation may have occurred. These two host populations are frequently used interchangeably as source populations for research. Euprymna scolopes is an important model organism and offers the opportunity to examine the interplay between a binary and a consortial symbiosis in a single model host. Understanding the inherent natural variability of this association will aid in our understanding of the conservation, function, transmission, and development of the ANG symbiosis.